Penilaian Beban Kerja Mental pada Staff Karyawan Gudang di PT. Pupuk Kujang Cikampek dengan Pendekatan Metode National Aeronautics and Space Administration-Task Load Index (NASA-TLX) - Ali, Dimas Nur; Sutrisno, Sutrisno; Nugraha, Billy (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2024)
The mental workload has a significant impact on work productivity, with heavier workloads leading to decreased worker productivity. Hence, to ensure optimal work output, it is crucial to address various factors related to human performance. This study, conducted at PT. Pupuk Kujang, utilized the National Aeronautics and Space Administration Task Load Index (NASA-TLX) method to assess mental workload. The findings indicate that the mental workload experienced by five employees in the Spare Parts Warehouse Department at PT. Pupuk Kujang Cikampek falls within the high classification, with an average Workload Weighted Load (WWL) score of 74.04, highlighting the need for work improvements. Potential enhancements can be implemented in several ways, such as developing job descriptions for guided activities, fostering motivation to boost employee morale, introducing employee rotation to alleviate work-related monotony and boredom, and implementing workload and time measurements to balance workloads among employees, thereby promoting overall employee performance.